PENGARUH KEPERCAYAAN DAN KUALITAS JASA TERHADAP KEPUASAN PELANGGAN DALAM MEMBENTUK LOYALITAS PELANGGAN PADA PT. ARPENI PRATAMA OCEAN LINE Tbk. CABANG SEMARANG - Victoria Diah Nugraeni; Putut - Haribowo (Admisi dan Bisnis, 2016)
PT. Arpeni Pratama Ocean Line Tbk is apublic company founded in Jakarta onOctober 4, 1975 which is engaged intransportation, opened a branch office inSemarang in 2004. To achieve the mission ofthe company is becoming the leading shippingcompany in Indonesia, the company needs topay attention on customer loyalty. However,in the year 2010-2014 the number ofcustomers decreased. The purpose of thisstudy is to know about: 1) the contribution oftrust and quality of services to satisfactiondirectly, 2) the contribution of trust, servicequality and customer satisfaction to customerloyalty both directly and indirectly. Theanalysis tools used are test of validity,reliability test, F test, T test, the coefficientdetermination and path analysis. From thedata, has obtained the equation coefficientcalculation line as follows: Y =0,424 X1 +0,232 X2 + 0,735 ɛ1 Based on the equation, itcan be seen that trust contributes greatly tocustomer satisfaction and 73,5% is thecontribution of other factors. The second pathcoefficient equation: Z =0,370X1+0,334X2+0,315Y+ 0,441 ɛ2 Based on the secondequation, it can be seen that trust gives agreat contribution to customer loyalty and44,1% is the contribution of other factors.